INTERPERSONAL METAPHOR OF MOOD IN ANTHONY DOERR’S NOVEL ALL THE LIGHT WE CANNOT SEE - Ali Sofyan; Sri Wulan (Universitas Islam Sumatera Utara, 2021)
This study aims to explore the transference of mood in interpersonal metaphor. The design method is descriptive and the approach is qualitative research. The main data are taken from the novel All the Light We Cannot See written by Anthony Doerr. The analysis is done by identifying the interpersonal metaphor of mood in the novel, describing them, and determining the dominant transference by using the percentage formula. 160 pages or one-third of the novel were taken as the data of this study. By completing the steps of the objectives, the significance is to give a thorough comprehension about interpersonal metaphor of mood and the transferences occurred in the sentences whether it is in texts or in speeches. The finding shows that the dominant mood found in the novel is declarative which reaches 44% occurrences. The second mood which often occurs in the novel is interrogative with 40%. The third is command in interrogative mood with 12%occurences and the statement in imperative mood follows with 4% occurrences; while there two patterns which cannot be found in the novel. They are question in declarative mood and imperative mood. It implies that most sentences in the novel give command in declarative form.